Aqueous extract of Artemisia capillaris improves non-alcoholic fatty liver and obesity in mice induced by high-fat diet - Liang, Meng; Huo, Mohan; Guo, Yi; Zhang, Yuyi; Xiao, Xiao; Xv, Jianwen; Fang, Lixue; Li, Tianqi; Wang, Huan; Dong, Siyu; Jiang, Xiaowen; Yu, Wenhui (Frontiers in Pharmacology, 2022)
Non-alcoholic fatty liver disease (NAFLD) is one of the most common chronic liver diseases and is a nutritional metabolic disease. Artemisia capillaris (AC) is the above-ground dried part of Artemisia capillaris Thunb. or Artemisia scoparia Waldst. et Kit., a natural medicinal plant with pharmacological effects of heat-clearing and biliary-promoting. In order to evaluate the therapeutic effect of Artemisia capillaris on NAFLD and obesity, experiments were conducted using aqueous extracts of Artemisia capillaris(WAC) to intervene in NAFLD models in vivo and in vitro. In vivo experiments were performed using HFD-fed(high fat diet) C57BL/6 mice to induce NAFLD model, and in vitro experiments were performed using oleic acid to induce HepG2 cells to construct NAFLD cell model. H.E. staining and oil red O staining of liver tissue were used to observe hepatocytes. Blood biochemistry analyzer was used to detect serum lipid levels in mice. The drug targets and mechanism of action of AC to improve NAFLD were investigated by western blotting, qRT-PCR and immunofluorescence. The results showed that C57BL/6 mice fed HFD continuously for 16 weeks met the criteria for NAFLD in terms of lipid index and hepatocyte fat accumulation. WAC was able to reverse the elevation of serum lipid levels induced by high-fat diet in mice. WAC promoted the phosphorylation levels of PI3K/AKT and AMPK in liver and HepG2 cells of NAFLD mice, inhibited SREBP-1c expression, reduced TG and lipogenesis, and decreased lipid accumulation. In summary, WAC extract activates PI3K/AKT pathway, reduces SREBP-1c protein expression by promoting AMPK phosphorylation, and decreases fatty acid synthesis and TG content in hepatocytes. AC can be used as a potential health herb to improve NAFLD and obesity.